Smart Home Area Networks Protocols within the Smart Grid Context - Hafeez, Ayesha (2014)
The Internet of things (IoT) applications are becoming one of the emerging smart grid enabling technologies. Smart home appliances are one the beneficiary of such applications. Machine-to-Machine and Man-to-Machine are the basic IoT communication platforms that enable home appliances to communicate with each other to be more efficiently operated. In a recent search for the IoT communication protocols that are utilized in smart home appliances, there was no inclusive reference that contains and describes the smart home area networks and guides the research and development (R&D) professionals to select the suitable protocol for an application. This paper presents a comprehensive review of the home area network (HAN) communication protocols that are used to enable bidirectional communication between the home owners, utilities and smart home appliances. The paper presents the most utilized HANs wired and wireless communication protocols and discusses their characteristics, advantages and disadvantages.